Network localization of limb ataxia based on causal brain lesions - Liesmäki, Oliver (My University, 2023)
Ataxia is considered to originate from the cerebellum but can also occur without obvious cerebellar damage, such as in individuals with anterior circulation stroke, where the mechanisms underlying ataxia are not clear. The aim of this study was to identify the neural substrates of limb ataxia based on causal stroke lesions. Two hundred patients with new-onset stroke were prospectively enrolled into the study. The patients were examined 1) right after their stroke (baseline), and 2) approximately 3 months later (follow-up) to assess limb ataxia. Stroke lesion locations and their functional connectivity, computed using an external dataset of 1,000 healthy volunteers, were compared voxel-by-voxel across the whole brain between patients with and without ataxia. Thirty-five patients had new-onset acute limb ataxia and seven at follow-up. More than 50% of the lesions causing ataxia were located outside the cerebellum and cerebellar peduncles, and there were no lesion locations significantly associated with ataxia. Lesions causing ataxia were connected to a common network defined by connectivity to the intermediate zone cerebellar structures, including the interposed and dentate nuclei. The results were similar when analysing acute ataxia or ataxia at any time, controlling for covariates, and including only lesions outside the cerebellum and cerebellar peduncles, and showed expected laterality when analysing left- and right-sided ataxia separately. Brain lesions causing limb ataxia occur in heterogenous locations but are connected to a common network with a hub in the intermediate zone of the cerebellum. These findings can aid in clinical localization of lesions causing limb ataxia and identify the neural substrates of limb ataxia.